2005
DOI: 10.1149/1.2050607
|View full text |Cite
|
Sign up to set email alerts
|

Characteristic Thickness for a Dense La[sub 0.8]Sr[sub 0.2]MnO[sub 3] Electrode

Abstract: Dense La 0.8 Sr 0.2 MnO 3 ͑LSM͒ electrodes were patterned by photolithography and fabricated via pulsed-laser deposition on Y 2 O 3-stabalized ZrO 2 ͑YSZ͒ electrolytes. Impedance analysis shows that the interfacial polarization resistance decreases significantly as electrode thickness drops below a critical value, beyond which the top surface of the LSM becomes active for oxygen reduction. However, when the LSM electrodes become too thin, the in-plane sheet resistance of the LSM starts to limit the utilization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
45
1

Year Published

2006
2006
2010
2010

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 35 publications
6
45
1
Order By: Relevance
“…Because the contribution of surface oxygen exchange ͑LF1͒ to the total impedance is comparable to that of mixed TPB/bulk charge transfer ͑LF2͒ for microelectrode thickness of 240 nm, it is proposed that a LSM80-20 microelectrode with thickness of Ͻ240 nm can be considered as an effective mixed conductor. It should be mentioned that the critical thickness of 240 nm is lower than that ͑360 nm͒ reported previously by Koep et al 30 at 700°C. This difference might be attributed to the fact that LSM80-20 microelectrodes in this work can have different microstructure and surface chemical compositions from this previous study, which could greatly affect the surface exchange and TPB/bulk charge transfer, respectively.…”
Section: B83contrasting
confidence: 56%
See 3 more Smart Citations
“…Because the contribution of surface oxygen exchange ͑LF1͒ to the total impedance is comparable to that of mixed TPB/bulk charge transfer ͑LF2͒ for microelectrode thickness of 240 nm, it is proposed that a LSM80-20 microelectrode with thickness of Ͻ240 nm can be considered as an effective mixed conductor. It should be mentioned that the critical thickness of 240 nm is lower than that ͑360 nm͒ reported previously by Koep et al 30 at 700°C. This difference might be attributed to the fact that LSM80-20 microelectrodes in this work can have different microstructure and surface chemical compositions from this previous study, which could greatly affect the surface exchange and TPB/bulk charge transfer, respectively.…”
Section: B83contrasting
confidence: 56%
“…[8][9][10][11] Therefore, numerous studies have employed porous, high-surface-area electrodes with nanometer-scale LSM particle sizes [12][13][14] or composite LSM-YSZ 3,15,16 to enhance overall TPB length and thus lower ORR resistance and overpotential. However, it is not apparent how LSM particle sizes alter the rate-limiting reaction of ORR and the contributions of the TPB and bulk pathway 6,17,18 as a function of temperature, which limits the efficiency optimization of porous electrodes for intermediate temperature operation.Electrodes with well-defined geometries, such as dense coneshaped pellets, 19-21 thin films, 22-25 and patterned microelectrodes, [26][27][28][29][30][31][32][33] have been used to provide simple scaling relationships between ORR impedance and electrode dimensions, such as TPB length. Mizusaki et al 6 first demonstrated that oxygen-ion diffusion can occur through dense, oxygen-over-stoichiometric LSM electrodes having thickness of 1-2 m at 700-900°C.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In most instances a reference electrode is retained as part of the configuration. [4][5][6][7][8][9] In contrast to this trend, Fleig and co-workers [10][11][12][13][14] have adopted a point electrode geometry that is explicitly reference-less. For dense, surface-limited electrodes, the assumption that the point geometry has effectively eliminated the contribution of the counter electrode is likely valid.…”
Section: Introductionmentioning
confidence: 99%